On the reliability of long period response spectral ordinates from digital accelograms. - Paolucci, Roberto (Earthquake engineering & structural dynamics.)
Using records from co-located broadband and digital strong motion (SM) instruments, it is first shown that the displacement waveforms obtained by double integration of the accelogram need not be free of unrealistic baseline drift to yield reliable spectral ordinates up to at least 10s. Secondly, to provide objective criteria for selecting reliable digital SM records for ground motion predictions at long periods, a set of synthetic accelograms contaminated by random long period noise has been used, and the difference between the original accelograms and the spurious ones in terms of response spectra has been quantified, by introducing a noise index that can be easily calculated based on the velocity waveform of the record. The results of this study suggest that high pass filtering the digital acceleration record from a cutoff period selected to suppress baseline drifts on the displacement waveform appears to be in most cases too conservative and unduly depletes reliable information on long period spectral ordinates.